Laboratory Measurement and Interpretation of the Changes of Physical Properties after Heat Treatment in Tight Porous Media - Yili Kang; Mingjun Chen; Lijun You; Xiangchen Li (Journal of Chemistry)
Prevention of water blocking and optimization of multiscale flow channels will increase gas production of tight reservoirs. Physical properties of samples from representative tight gas reservoirs were measured before and after high temperature treatment. Results show that, with the increase of treatment temperature, mass decreases, acoustic transit time increases, and permeability and porosity increase. Permeability begins to increase dramatically if treatment temperature exceeds the threshold value of thermal fracturing, which is 600~700°C, 500~600°C, 300~500°C, and 300~400°C for shale, mudstone, tight sandstone, and tight carbonate rock, respectively. Comprehensive analyses indicate that the mechanisms of heat treatment on tight porous media include evaporation and dehydration of water, change of mineral structure, generation of microfracture, and network connectivity. Meanwhile, field implementation is reviewed and prospected. Interpretations indicate that, according to the characteristics of multiscale mass transfer in tight gas formation, combining heat treatment with conventional stimulation methods can achieve the best stimulation result.